Determinants of employees' creativity: Modeling the mediating role of organizational motivation to innovate - Yohannes Mekonnen Yesuf; Demis Alamirew Getahun; Asemamaw Tilahun Debas (Journal of Innovation and Entrepreneurship, 2024)
The study aims to empirically investigate the effects of the work environment and family-work resource spillover on employees' creativity in agricultural research institutes. Additionally, this research proposes to examine the mediating role of organizational motivation to innovate in the relationships between the work environment and family-work resource spillover on employees' creativity. Using a sample of 302 researchers from agricultural research institutes in Ethiopia, the hypothesized relationships were tested through the partial least squares structural equation modeling (PLS-SEM) technique. The results reveal significantly positive direct effects of work group support and family-work resource spillover on employees' creativity. However, the results did not confirm the direct relationships of factors such as sufficient resources, reliable workload pressure, freedom, challenging work, managerial encouragement, and employees' creativity. The findings of the study contribute to our understanding of work contexts in agricultural research institutes and suggest ways in which administrators can create a conducive working environment to enhance employees' creativity.
Keywords: 650; Creativity; Factors of work environment; Organizational motivation to innovate and family-work resource spillover